From mental hygiene to mental health: ideology, discourses and practices in Franco's Spain (1939–75). Issue 4 (December 2017) - Novella, Enric J; Campos, Ricardo
Based on an analysis of the discourses, the ideological appropriation and the practical influence of mental hygiene in Spanish psychiatry during the early years of the Francoist regime, this article examines its decline and subsequent replacement by the new concept of mental health promoted by the World Health Organization and other international bodies from the mid-twentieth century. The old approach, essentially focused on the prophylaxis of insanity within the framework of a set of interventionist policies of social defence, was thus transformed from the beginning of the 1960s into a much more ambitious and comprehensive project which sought to promote the psychosocial balance and performance of individuals in the context of increasingly socialized health-related discourses and networks of care.